QRIS ON THE RISE: THE ROLE OF PERCEIVED USEFULNESS, SECURITY, AND SOCIAL FACTORS ON INTENTION TO USE QRIS AS TRANSACTION PAYMENT INSTRUMENT IN GENBI SULUT - Monintja, Steve Christofel; Tulung, Joy Elly; Pandowo, Merinda H. Ch. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The rapid growth of digital payment systems has transformed financial transactions globally, with the Quick Response Code Indonesian Standard (QRIS) serving as a key initiative by Bank Indonesia to unify payment methods across providers. This study analyzes the role of perceived usefulness, security, and social factors on the intention to use QRIS among 148 GenBI Sulut members. Using a quantitative approach, the data were collected via a structured questionnaire and analyzed through multiple linear regression with Statistical Package for the Social Sciences (SPSS) version 26, following validity, reliability, and classical assumption tests. Results show that perceived usefulness significantly increases intention to use, while security and social factors have no significant partial effects; however, all three variables jointly have a significant influence, explaining 65.5% of variance. The findings validate the Technology Acceptance Model (TAM) and suggest that QRIS adoption strategies should focus on enhancing perceived usefulness, ensuring security, and delivering positive user experiences.   Keywords: QRIS, Perceived Usefulness, Security, Social Factors, Intention to Use